ETHICS OF WAR IN THE CONTEXT OF THE ACTIONS OF THE ARMED FORCES OF UKRAINE: ANALYSIS OF DILEMMAS AND DECISION-MAKING IN COMBAT CONDITIONS - Vozniak, Inna; Myronenko, Natalia (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . Amidst the ongoing armed conflict in Ukraine, the adherence of the Ukrainian Armed Forces (UAF) to the ethical standards of warfare and the norms of international humanitarian law has become increasingly relevant. Despite legal regulations, the moral dilemmas of combat operations demand in-depth academic reflection. M e t h o d s . The study is based on qualitative analysis of official documents and media publications, case studies, ethical analysis, and a survey of military personnel. R e s u l t s . The article presents the results of a survey of 42 UAF service members aimed at identifying the moral and ethical dilemmas they face while performing their duties, and the specifics of decision-making in complex combat situations. The study revealed a number of key issues, including discrepancies between official information and frontline realities, the need to balance standard procedures with non-standard solutions, the reconsideration of civilian moral values in a military context, confrontation with the brutal reality of war versus romanticised expectations, conflicts between religious beliefs and military duties, a reassessment of concepts such as justice and order, and reflections on personal survival and willingness to self-sacrifice. The findings indicate the continuous presence of complex moral and ethical challenges in the operational activities of UAF personnel, which require deep reflection and reasoning for effective decision-making under combat conditions. The originality of this study lies in its focused analysis of ethical dilemmas specifically experienced by Ukrainian military personnel within the context of the Russian-Ukrainian war, supported by empirical data gathered from their combat experience and an attempt to integrate psychological, social, and legal aspects within an interdisciplinary framework. C o n c l u s i o n s . The results contribute to a deeper understanding of the significance of ethics in warfare and justify the necessity of enhancing ethical training, strengthening compliance with humanitarian law, and providing psychological support to military personnel. This is critical not only for upholding moral standards but also for sustaining Ukraine’s international reputation.